Development of Adaptive Physical Education Learning Model Through Visual Media for Deaf Students - Yan Indra Siregar; Ahmad Syabaruddin Ahmad Syabaruddin; Muhammad Farel Ramadhan; Ferry Hendri Carlos Panggabean Ferry Hendri Carlos Panggabean; Tiara Apulita Br Kaban Tiara Apulita Br Kaban; Milwanto Hutapea Milwanto Hutapea (Jurnal Pendidikan Jasmani (JPJ), 2026)
This research aims to develop an adaptive physical education learning model by utilizing visual media intended for deaf students. Students with hearing impairments often experience limitations in understanding verbal instructions that are generally used by teachers in the physical education learning process. Through visual media in the form of pictures, animations, and demonstration videos, it is hoped that students can understand movements, rules, and learning strategies more optimally. The research method used is Research and Development (R&D) with the Borg & Gall development model consisting of ten stages, but this research is limited to a limited trial stage. The subjects of the study were deaf students in special schools (SLB) with a total of 15 students. The results of the study show that visual media provides an increase in understanding of movement instruction, learning motivation, and student participation in physical education activities. Thus, visual media-based learning models can be used as an alternative to innovation in adaptive physical education learning for deaf students.